The Allocation of European Union Allowances: Lessons, Unifying Themes and General Principles - Barbara K. Buchner; Carlo Carraro; A. Denny Ellerman (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper is the concluding chapter of Rights, Rents and Fairness: Allocation in the European Emissions Trading Scheme, edited by the co-authors and forthcoming from Cambridge University Press. The main objective of this paper is to distill the lessons and general principles to be learnt from the allocation of allowances in the European Union Emission Trading Scheme (EU ETS), i.e. in the worlds first experience with allocating carbon allowances to sub-national entities. We discuss the lessons that emerge from this experience and make some comments on what seem to be more general principles informing the allocation process and on what are the global implications of the EU ETS. As has become obvious during the first allocation phase, the diversity of experience among the Member States is considerable, so that it must be understood that these lessons and unifying themes are drawn from the experience of most of the Member States, not necessarily from all. Lessons and unifying observations are grouped in three categories: those concerning the conditions encountered, the processes employed, and the actual choices.
Keywords: C72; H23; Q25; Q28; 330; Climate Change; Emission Trading; Allocation; Fairness; EU Policy; Allokation; Gerechtigkeit; EU-Politik; EU-Staaten; Emissionshandel